THE EFFECT OF ATTITUDES TOWARDS THE CONCEPT OF COLLABORATIVE CONSUMPTION ON INTENTION TO USE SECOND HAND E-FASHION WEBSITES - Cizer, Ece Ozer; Ozcan, Burcu Mucan (MEHMET AKIF ERSOY UNIV, 2021)
The main aim of the study is to examine the mediating effect of attitudes towards collaborative consumption on the effect of economic benefit, sustainability, trust, eWOM and price sensitivity on the intention of using second-hand e-fashion sites. Previous studies in Turkey that related collaborative consumption have focused on the car and home-sharing. In this study, second-hand fashion sites were examined within the scope of collaborative consumption. Therefore this study distinguishes from its peers in the literature. The data of the study was obtained by collecting questionnaires from 316 participants and a structural equation model with seven variables was established. Reliability and validity analysis, con elation analysis, exploratory factor analysis, confirmatory factor analysis and path analysis were performed in the study. As a result of the study, it was seen that economic benefit, sustainability, trust, eWOM and price sensitivity positively affect attitudes and intention to use on collaborative consumption. In addition, it was found that the attitudes towards the concept of collaborative consumption had a mediating effect between the independent variables and intention to use as a dependent variable.
Keywords: Sharing Economy; Collaborative Consumption; Second-Hand Shopping; WORD-OF-MOUTH; MEDIATING ROLE; TRUST; IMPACT; Business & Economics